# How do you solve #7x - ( x - 3) = 3( x + 10)#?

##### 4 Answers

x=9

#### Explanation:

First, multiply the brackets

Calculate the "

Take away the

Take away the

Divide both sides by

#### Explanation:

#"distribute brackets on both sides of the equation"#

#7x-x+3=3x+30#

#6x+3=3x+30#

#"subtract "3x" from both sides"#

#6x-3x+3=30#

#3x+3=30#

#"subtract 3 from both sides"#

#3x=30-3=27#

#"divide both sides by 3"#

#rArrx=27/3=9#

#color(blue)"As a check"# Substitute this value into the equation and if both sides are equal then it is the solution.

#"left "=63-(9-3)=63-6=57#

#"right "=3(9+10)=3xx19=57#

#x=9" is the solution"#

#### Explanation:

We can distribute the parenthesis on the left and right to get

Next, let's combine the left side variables to get

Next, let's subtract

This is unconventional, but since all terms are divisible by

Subtracting

Hope this helps!